Ru complexes of Hoveyda–Grubbs type immobilized on lamellar zeolites: activity in olefin metathesis reactions - Balcar, Hynek; Žilková, Naděžda; Kubů, Martin; Mazur, Michal; Bastl, Zdeněk; Čejka, Jiří (Beilstein Journal of Organic Chemistry, 2015)
Hoveyda–Grubbs type catalysts with cationic tags on NHC ligands were linker-free immobilized on the surface of lamellar zeolitic supports (MCM-22, MCM-56, MCM-36) and on mesoporous molecular sieves SBA-15. The activity of prepared hybrid catalysts was tested in olefin metathesis reactions: the activity in ring-closing metathesis of citronellene and N,N-diallyltrifluoroacetamide decreased in the order of support MCM-22 ≈ MCM-56 > SBA-15 > MCM-36; the hybrid catalyst based on SBA-15 was found the most active in self-metathesis of methyl oleate. All catalysts were reusable and exhibited low Ru leaching (<1% of Ru content). XPS analysis revealed that during immobilization ion exchange between Hoveyda–Grubbs type catalyst and zeolitic support occurred in the case of Cl− counter anion; in contrast, PF6− counter anion underwent partial decomposition.
Keywords: Hoveyda–Grubbs type catalyst; hybrid catalysts; lamellar zeolites; non-covalent immobilization; olefin metathesis

(untitled) - Buchmeiser, M. R. (Chem. Rev., 2009)

(untitled) - Copéret, C.; Basset, J.-M. (Adv. Synth. Catal., 2007)

New and Future Developments in Catalysis. Hybrid Materials, Composites, and Organocatalysts - Balcar, H.; Roth, W. J. (Hybrid Catalysts for Olefin Metathesis and Related Polymerizations, 2013)

Olefin Metathesis, Theory and Practice - Buchmeiser, M. R. (Immobilization of Olefin Metathesis Catalysts, 2014)

(untitled) - Balcar, H.; Čejka, J. (Coord. Chem. Rev., 2013)

(untitled) - Bek, D.; Balcar, H.; Žilková, N.; Zukal, A.; Horáček, M.; Čejka, J. (ACS Catal., 2011)

(untitled) - Pastva, J.; Čejka, J.; Žilková, N.; Mestek, O.; Rangus, M.; Balcar, H. (J. Mol. Catal. A: Chem., 2013)

(untitled) - Shinde, T.; Varga, V.; Polášek, M.; Horáček, M.; Žilková, N.; Balcar, H. (Appl. Catal., A, 2014)

(untitled) - Drozdzak, R.; Allaert, B.; Ledoux, N.; Dragutan, I.; Dragutan, V.; Verpoort, F. (Coord. Chem. Rev., 2005)

(untitled) - Zhang, H.; Li, Y.; Shao, S.; Wu, H.; Wu, P. (J. Mol. Catal. A: Chem., 2013)

(untitled) - Li, L.; Shi, J.-l. (Adv. Synth. Catal., 2005)

(untitled) - Elias, X.; Pleixats, R.; Man, M. W. C. (Tetrahedron, 2008)

(untitled) - Dragutan, I.; Dragutan, V. (Platinum Met. Rev., 2008)

(untitled) - Van Berlo, B.; Houthoofd, K.; Sels, B. F.; Jacobs, P. A. (Adv. Synth. Catal., 2008)

(untitled) - Yang, H.; Ma, Z.; Wang, Y.; Wang, Y.; Fang, L. (Chem. Commun., 2010)

(untitled) - Balcar, H.; Shinde, T.; Žilková, N.; Bastl, Z. (Beilstein J. Org. Chem., 2011)

(untitled) - Schachner, J. A.; Cabrera, J.; Padilla, R.; Fischer, C.; van der Schaaf, P. A.; Pretot, R.; Rominger, F.; Limbach, M. (ACS Catal., 2011)

(untitled) - Cabrera, J.; Padilla, R.; Bru, M.; Lindner, R.; Kageyama, T.; Wilckens, K.; Balof, S. L.; Schanz, H.-J.; Dehn, R.; Teles, J. H.; Deuerlein, S.; Müller, K.; et al. (Chem. – Eur. J., 2012)

(untitled) - Cabrera, J.; Padilla, R.; Dehn, R.; Deuerlein, S.; Gułajski, Ł.; Chomiszczak, E.; Teles, J. H.; Limbach, M.; Grela, K. (Adv. Synth. Catal., 2012)

(untitled) - Bru, M.; Dehn, R.; Teles, J. H.; Deuerlein, S.; Danz, M.; Müller, I. B.; Limbach, M. (Chem. – Eur. J., 2013)

(untitled) - Pastva, J.; Skowerski, K.; Czarnocki, S. J.; Žilková, N.; Čejka, J.; Bastl, Z.; Balcar, H. (ACS Catal., 2014)

(untitled) - Skowerski, K.; Pastva, J.; Czarnocki, S. J.; Janoscova, J. (Org. Process Res. Dev., 2015)

(untitled) - Roth, W. J.; Nachtigall, P.; Morris, R. E.; Čejka, J. (Chem. Rev., 2014)

(untitled) - Choi, M.; Na, K.; Kim, J.; Sakamoto, Y.; Terasaki, O.; Ryoo, R. (Nature, 2009)

(untitled) - Eliášová, P.; Opanasenko, M.; Wheatley, P. S.; Shamzhy, M.; Mazur, M.; Nachtigall, P.; Roth, W. J.; Morris, R. E.; Čejka, J. (Chem. Soc. Rev., 2015)

(untitled) - Roth, W. J.; Čejka, J. (Catal. Sci. Technol., 2011)

(untitled) - Roth, W. J.; Nachtigall, P.; Morris, R. E.; Wheatley, P. S.; Seymour, V. R.; Ashbrook, S. E.; Chlubná, P.; Grajciar, L.; Položij, M.; Zukal, A.; Shvets, O.; Čejka, J. (Nat. Chem., 2013)

(untitled) - Morris, R. E.; Čejka, J. (Nat. Chem., 2015)

(untitled) - Zukal, A.; Dominguez, I.; Mayerová, J.; Čejka, J. (Langmuir, 2009)

(untitled) - Opanasenko, M.; Štěpnička, P.; Čejka, J. (RSC Adv., 2014)

(untitled) - Juttu, G. G.; Lobo, R. F. (Microporous Mesoporous Mater., 2000)

(untitled) - Díaz, U.; Corma, A. (Dalton Trans., 2014)

(untitled) - Phan, N. T. S.; Van Der Sluys, M.; Jones, C. W. (Adv. Synth. Catal., 2006)

(untitled) - Chatterjee, A. K.; Choi, T.-L.; Sanders, D. P.; Grubbs, R. H. (J. Am. Chem. Soc., 2003)

(untitled) - Nelson, D. J.; Manzini, S.; Urbina-Blanco, C. A.; Nolan, S. P. (Chem. Commun., 2014)

U.S. Patent - Kresge, C. T.; Roth, W. J.; Simmons, K. G.; Vartuli, J. C. (Crystalline Oxide Material, 1993)

U.S. Patent - Fung, A. S.; Lawton, S. L.; Roth, W. J. (Synthetic Layered MCM-56, Its Synthesis And Use, 1994)

(untitled) - Roth, W. J.; Kresge, C. T.; Vartuli, J. C.; Leonowicz, M. E.; Fung, A. S.; McCullen, S. B. (Stud. Surf. Sci. Catal., 1995)

(untitled) - Topka, P.; Balcar, H.; Rathouský, J.; Žilková, N.; Verpoort, F.; Čejka, J. (Microporous Mesoporous Mater., 2006)

(untitled) - Shirley, D. A. (Phys. Rev. B, 1972)

(untitled) - Scofield, J. H. (J. Electron Spectrosc. Relat. Phenom., 1976)

Surface Analysis by Auger and X-Ray Photoelectron Spectroscopy - Briggs, D. J.; Grant, T. (Cromwell Press, 2003)